Exploring and Developing a New Culturally-Appropriate Diabetes Distress Scale in Taiwan - Lin, Ching-Ling; Chang, Yao-Tsung; Liu, Wen-Cheng; Huang, Li-Chi; Tsao, Shin-Yi; Chen, Yu-Hsin; Chen, Ruey-Yu (Frontiers in Public Health, 2022)
Introduction: The aim of this study was to develop and validate a new diabetes distress scale suitable for Chinese and Taiwanese culture. Methods: This study collected the current diabetes distress measurement tools, re-organized current definitions about the domains of diabetes distress, and then developed a new tool. 395 participants from four hospitals in northern Taiwan were recruited by cluster randomized sampling for validity test. Results: We found the new diabetes distress scale had appropriate reliability and validity, including an acceptable model fit for the 12-item scale. Conclusions: This new diabetes distress scale might be more directly related to emotional distress issues and blood sugar control and improve the prevention and treatment of diabetes distress and even benefit the treatment of diabetes. More validity and reliability studies about this new tool in wider countries are needed.